2009
DOI: 10.1097/inf.0b013e31819b592e
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of Nucleic Acid Amplification Tests for Detection of Chlamydia trachomatis and Neisseria gonorrhoeae in Children Being Evaluated for Sexual Abuse

Abstract: These results suggest that NAATs on urine, with confirmation, are adequate for use as a new forensic standard for diagnosis of CT and NG in children suspected of sexual abuse. Urine NAATs offer a clear advantage over culture in sensitivity and are less invasive than swabs, reducing patient trauma and discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 17 publications
0
56
0
1
Order By: Relevance
“…41 However, a recent multicenter study found that commercially available nucleic acid amplification tests (NAATs) are highly sensitive and specific for these organisms and that these tests provide "a better alternative than culture as a forensic standard." 63 The study also found that NAATs performed on urine specimens worked as well as vaginal swabs to detect infection in both prepubertal and postpubertal girls, obviating more invasive tests. All positive NAAT results in this study were confirmed by genotypic and sequence analysis tests, leading to a high positive predictive value for C trachomatis and N gonorrhoeae.…”
Section: Testing For Stismentioning
confidence: 85%
“…41 However, a recent multicenter study found that commercially available nucleic acid amplification tests (NAATs) are highly sensitive and specific for these organisms and that these tests provide "a better alternative than culture as a forensic standard." 63 The study also found that NAATs performed on urine specimens worked as well as vaginal swabs to detect infection in both prepubertal and postpubertal girls, obviating more invasive tests. All positive NAAT results in this study were confirmed by genotypic and sequence analysis tests, leading to a high positive predictive value for C trachomatis and N gonorrhoeae.…”
Section: Testing For Stismentioning
confidence: 85%
“…To date, there have been three published studies that compared NAAT results to those of N. gonorrhoeae culture for children being evaluated for suspected sexual abuse (9,35,42). All these studies included urine specimens as well as vaginal swabs.…”
Section: Nucleic Acid Amplification Testsmentioning
confidence: 99%
“…Recently, the Centers for Disease Control and Prevention (CDC) conducted a multicenter study of diagnostic tests for STIs in children under evaluation of sexual abuse (15,16). One of the objectives of this study was to evaluate the use of NAATs for the detection of N. gonorrhoeae and C. trachomatis in noninvasive specimens for clinical and forensic purposes.…”
mentioning
confidence: 99%
“…Among the 8 singleround PCR assays, only one primer pair, TVC11/TVC12, was positive for all 4 specimens, and among the 4 nested PCRs, only 2 primer sets (TVC3F/TVC4R and TVC11F/TVC; TVC5F/TV6R and TV7F/C8R) were positive for all 4 specimens. We selected the nested primer sets TVC3F/TVC4R and TVC11F/TVC12R to screen urine specimens from the CDC multicenter study on STIs in children being evaluated for sexual abuse (15,16). Of the 485 female study participants enrolled in the original study (15,16), only 406 had specimens remaining for this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation